Penerapan Model Pembelajaran Kooperatif Tipe Kancing Gemerincing (Talking Chips) dalam Meningkatkan Hasil Belajar IPA Peserta Didik di Sekolah Dasar - Hasrin Lamote; Resti Resti; Moh. Yahya Obaid; Marlina Marlina (IAIN Kendari, 2021)
This study aims to improve science learning outcomes of the Natural science in Ivc grade students at SDN 02 Kendari through the aplication of the talkng Chips cooperative learning. This type of research is classroom action research (PTK), which is carried out in two cycles, in IVC Class students in the odd semester of the school year 2019/2020. The research procedure includes planning the implementation of observasion, evaluation, and reflection techniques collecting data using the observasion of learning outcomes tests and dokumentation which were analized deskriptively. The resulth showed that : 1) the application of the talking chips model can increase in the activity of teachers and students so that teachers activity increases to 100% and student activity becomes 95%. 2) The learning outcomes of student can be improved through the aplication of the cooperative learning model of the jingling button type talking chips this can be proven in the percentage of student learning outcomes that reached 96%. Keywords : Jingle buttons, science learning outcomes, elementary schools